Prediction of Parkinson's disease tremor onset using artificial neural networks - Pan, S; Warwick, K; Stein, J; Gasson, M; Wang, S; Aziz, T; Burgess, J (2007)
In this paper we present the initial results using an artificial neural network to predict the onset of Parkinson's Disease tremors in a human subject. Data for the network was obtained from implanted deep brain electrodes. A tuned artificial neural network was shown to be able to identify the pattern of the onset tremor from these real time recordings.